Evaluation of Sleep Disturbances Prevalence in a Period of 6 Months after Recovery Post Covid-19 Patients Admitted to the Intensive Care Unit with Pulmonary Involvement of more than 20% - Nima Mohamadi Afrakoti; Aylin Hefzollesan; Mohammadsadegh Talebi Kahdouei; Seyyed Mojtaba Marashi; Arash Heroabadi; Samaneh Hajy Mola Rabi; Fatemeh Aghaei (Archives of Anesthesia and Critical Care)
Background: The emergence of COVID-19 in late 2019 swiftly led to a global pandemic, prompting urgent investigation into its multifaceted impacts. While prior studies have highlighted compromised sleep quality in hospitalized COVID-19 patients, this research delves into the enduring effects on sleep patterns for those with severe pulmonary involvement post-intensive care. This study addresses a critical gap in understanding the long-term consequences of the virus, emphasizing the importance of post-recovery care. Methods: Conducted as a cross-sectional study, we consecutively enrolled COVID-19 patients with over 20% pulmonary involvement admitted to the ICU at Shariati Hospital, Tehran, between June 2021 and January 2022. Demographic and clinical data were extracted from hospital records. After ethics committee approval, participants were contacted six months post-discharge to assess sleep quality using the Pittsburgh Sleep Quality Index (PSQI). Exclusions comprised obstructive sleep apnea patients and those with incomplete records. Results: Of the 60 eligible post-COVID-19 patients, 56 participated. Three individuals were unresponsive to calls, while one declined. Participants, primarily female (64.3%), had a mean age of 51.7 years. Notably, 80.4% exhibited sleep disorders six months post-discharge. Gender differences were observed, with females reporting higher scores in specific sleep quality components. Intriguingly, single individuals demonstrated a higher preference for sleep medication. These findings underscore the imperative for targeted interventions to improve post-ICU sleep quality in severe COVID-19 cases. Conclusion: The high prevalence of sleep disorders six months post-discharge underscores the enduring impact of COVID-19 on sleep quality. These findings call for targeted interventions and comprehensive post-ICU care protocols that prioritize sleep health.